1992
DOI: 10.1093/fampra/9.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centredness: Is It Applicable Outside the West? Its Measurement and Effect on Outcomes

Abstract: Patient-centredness has been shown to be associated with improved patient outcomes in the West. The objectives of this study were: (i) to further test a specific method for measuring patient-centredness that had previously demonstrated validity and reliability, and (ii) to test the effectiveness of a patient-centred approach amongst poor, non-Western people in South Africa. Patient-centredness was measured in terms of the practitioner's facilitation of the patient's reasons for coming, including symptoms, thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 0 publications
0
37
0
5
Order By: Relevance
“…Furthermore, the patient's views can assist the physician in making a diagnosis (Peppiatt, 1992). Research shows that the extent of a physician's patient-centredness contributes to the improvement of somatic complaints in patients with headaches, rheumatism, gastric ulcer, diabetes and breast cancer (Bertakis et al, 1998;Greenfield et al, 1985;the Headache study, 1986;Henbest & Fehrsen, 1992;Henbest & Stewart, 1990;Kaplan et al, 1989;Lorig et al, 1993;Rost et al, 1991).…”
Section: Patient-centrednessmentioning
confidence: 99%
“…Furthermore, the patient's views can assist the physician in making a diagnosis (Peppiatt, 1992). Research shows that the extent of a physician's patient-centredness contributes to the improvement of somatic complaints in patients with headaches, rheumatism, gastric ulcer, diabetes and breast cancer (Bertakis et al, 1998;Greenfield et al, 1985;the Headache study, 1986;Henbest & Fehrsen, 1992;Henbest & Stewart, 1990;Kaplan et al, 1989;Lorig et al, 1993;Rost et al, 1991).…”
Section: Patient-centrednessmentioning
confidence: 99%
“…Following Henbest & Fehrsen (1992), who noted that scoring only a part of a consultation could be as reliable as scoring an entire consultation, preliminary observations with observation periods of 5 min, 10 min and the total length were carried out during 48 encounters. As 10-min observation periods proved to be very reliable compared with the observation of the total length (non-verbal communication between 0á61 and 0á92 and verbal communication between 0á80 and 0á93, Pearson's R), observation time was standardized and the ®rst 10 min were observed of each of the 181 nursing encounters.…”
Section: Reliability Of the Observationsmentioning
confidence: 99%
“…Arborelius and Bremberg [13] found that consultations, which both doctor and patient had a positive feeling about, took less time than consultations about which they had negative feelings. Concerning patient centeredness, Henbest and Fehrsen [14] found patient-centred consultations to be no longer than others. Observational studies revealed no difference in duration of the separate components of consultations, like history taking, examination, giving advice and social behaviour, in long versus short consultations [15].…”
Section: Introductionmentioning
confidence: 99%